Restorying COVID‐19: Faculty and graduate students teaching and learning in crisis. Issue 173 (2nd June 2022) - Gnanadass, Edith; Merriweather, Lisa R.
Abstract: Teaching and learning in times of crisis like the Coronavirus pandemic is less about crisis management and more about humanizing the crisis. Restorying COVID begins with understanding our students and ourselves as whole people, and their multidimensional needs—academic, socio‐emotional, and socio‐cultural, including racialization, social class, and gendered roles. As faculty, we need to rethink our work and intentionally move beyond the classroom into a humanity mindset consistent with decolonizing theory. We suggest doing this by using engaged pedagogy and profound learning to enact a Critical Capital Theory informed by an anti‐Black racism stance.